Strategic bioprocessing of A. protothecoides and C. sorokiniana using renewable feedstocks for targeted bioproduct and biodiesel generation - Eleni Krikigianni; Kyriakos Antoniadis; Paul Christakopoulos; Ulrika Rova; Leonidas Matsakas; Alok Patel (Energy Conversion and Management: X)
The focus on sustainability and circular economy renders the microalgal biorefinery concept highly attractive. Although the diversity of microalgal composition makes them ideal feedstocks, their metabolic versatility challenges bioprocess optimization. To address this, an integrated, strain-specific approach was used to evaluate key cultivation parameters (nitrogen source, C/N ratio, and light intensity) as their interactions affect growth performance and biochemical composition. Heterotrophic cultivation of A. protothecoides (AP) and C. sorokiniana (CS) in glucose showed enhanced cell growth with organic N-sources. Biomass was consistently elevated across C/N ratios from 5 to 60 with corn steep liquor (CSL) (8.1 g L-1) and yeast extract (YE) (7.0 g L-1), while with urea it maximized at C/N 5 (6.2 g L-1). Protein synthesis increased at C/N 5, whereas lipid accumulation at C/N 60. Beechwood hydrolysate, a renewable glucose alternative, produced an average of 4.1 g L-1 protein (C/N 5) and 3.5 g L-1 lipids (C/N 60) between YE and CSL. Mixotrophic cultivation indicated better photosynthetic adaptation of AP at C/N 5, yielding 13.2 g L-1 biomass at 400 μmol m-2 s-1, whereas at C/N 60 growth was favored at 50 μmol m-2 s-1. The fatty acid profile of microalgal oil revealed de novo biosynthesis of odd-chain fatty acids at C/N 5 in both cultivation modes, while biodiesel-grade lipids produced in heterotrophic condition. These findings advance microalgal bioprocessing by emphasizing the importance of fine-tuning cultivation strategies and utilizing renewable nutrients to maximize resource efficiency and optimize the biosynthesis of valuable bioproducts, such as proteins, pigments, carbohydrates, and high-quality lipids.